The Program Escola da Terra in the continuing education of teachers from rural and quilombola schools: sociocultural practices as generating themes in the teaching of school mathematics - Raquel de Carvalho; Kaled Sulaiman Khidir; Rogério Ribeiro Coelho (Universidade Federal do Norte do Tocantins, 2022)
The Escola da Terra Program is a State policy, involving the federal government, state and municipal governments, as well as social movements and Public Higher Education Institutions. It seeks to promote specific continuous formation of teachers to meet the needs of rural and quilombola schools. This article aims to report and analyze contributions of the Improvement Course Escola da Terra at UFT, Arraias Campus, in the formation of rural teachers in Tocantins, having as reference the Module: Mathematical Languages. We analyzed materials produced by course participants, contents and methodologies addressed in the formation. The investigation uses as a research instrument the field reports of the professionals involved in the project. The data were analyzed in the light of the theoretical framework that deals with rural education, ethnomathematics, sociocultural practices and initial and continuing teacher formation. We highlight the elaboration of the action projects of the course participants, the result of reflections on the contents discussed during online meetings and materialized in the community time in the schools where they work. Although there are many challenges, we recognize that the Project (UFT) and the Program (MEC) Escola da Terra have triggered formation processes, which seek to build spaces for dialogue and reflection on educational practices based on their contexts, in line with the principles of Rural Education.